2021
DOI: 10.1186/s12913-021-06259-w
|View full text |Cite
|
Sign up to set email alerts
|

The out-of-pocket burden of chronic diseases: the cases of Belgian, Czech and German older adults

Abstract: Background Out-of-pocket payments have a diverse impact on the burden of those with a higher morbidity or the chronically ill. As the prevalence of chronic diseases increases with age, older adults are a vulnerable group. The paper aims to evaluate the impact of chronic diseases on the out-of-pocket payments burden of the 50+ populations in Belgium, the Czech Republic and Germany. Methods Data from the sixth wave of the Survey of Health, Ageing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Female-headed households are more likely to face a burden of high OOP expenditures than their male-headed counterparts [ 31 ], due to having different demographic, sociological, and economic characteristics both in developed and developing countries [ 32 ]. Poor health status, disability, and severe or complicated illnesses or conditions often result in higher OOP health expenditures [ 33 , 34 , 35 ]. For instance, a study conducted in Germany, Belgium, and Czechia found that specific chronic diseases increase the overall OOP burden with a strong association for the medicine burden [ 33 ].…”
Section: Literature Review On Factors Influencing Oop Health Expenditurementioning
confidence: 99%
See 1 more Smart Citation
“…Female-headed households are more likely to face a burden of high OOP expenditures than their male-headed counterparts [ 31 ], due to having different demographic, sociological, and economic characteristics both in developed and developing countries [ 32 ]. Poor health status, disability, and severe or complicated illnesses or conditions often result in higher OOP health expenditures [ 33 , 34 , 35 ]. For instance, a study conducted in Germany, Belgium, and Czechia found that specific chronic diseases increase the overall OOP burden with a strong association for the medicine burden [ 33 ].…”
Section: Literature Review On Factors Influencing Oop Health Expenditurementioning
confidence: 99%
“…Poor health status, disability, and severe or complicated illnesses or conditions often result in higher OOP health expenditures [ 33 , 34 , 35 ]. For instance, a study conducted in Germany, Belgium, and Czechia found that specific chronic diseases increase the overall OOP burden with a strong association for the medicine burden [ 33 ]. Another study performed in Australia concluded that OOP health expenditures are common among senior Australians with chronic conditions, and this expenditure increases with the number of chronic conditions [ 34 ].…”
Section: Literature Review On Factors Influencing Oop Health Expenditurementioning
confidence: 99%
“…The inability to perform ADLs and IADLs implies further pressure on government expenditure, as long-term care assistance may be required 8 . In addition to government spending, out-of-pocket payments for individuals with chronic health conditions are higher due to increased health-care use, lower earnings due to disability, early retirement, and dependence on social security systems 9 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, several governments have sought to improve the health of the population while reducing the associated financial burden. However, the presence of universal healthcare access and extensive coverage does not completely eliminate the requirement for out-of-pocket (OOP) payments to receive healthcare goods and services [ 3 ]. OOP health expenditure refers to all payments spent on medical costs such as consultation fees, medicine, diagnosis, laboratory, radiology, and admission, along with other non-medical expenses such as transportation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the chronically ill have less generous health insurance coverage than the non-chronically ill as treatments for chronic conditions are usually of high cost [ 8 ]. These factors constrain household budgets, leading to a significant increase in the financial burden for households and individuals with chronic illness [ 3 ].…”
Section: Introductionmentioning
confidence: 99%